2023
DOI: 10.1039/d3ob00718a
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of temperature dependence of hydride kinetic isotope effects with donor–acceptor distances in two solvents of different polarities

Mingxuan Bai,
Rijal Pratap,
Sanaz Salarvand
et al.

Abstract: Shorter donor–acceptor distances (DADs) in hydride transfer reactions give rise to a weaker temperature (T) dependence of KIEs. This supports the debated proposal that links T-dependence of KIEs to DAD sampling catalysis studies in enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 63 publications
1
7
0
Order By: Relevance
“…We are the first to systematically investigate the said relationship using the “simpler” hydride transfer reactions in solution, and our results appear to be consistent with the proposed DAD−Δ E a relationship as well. In our studies, we use structural and solvent effects to modulate the rigidity of the systems and correlate the DAD information with the observed Δ E a ’s. We use the hydride transfer reactions of NADH/NAD + analogues for the study.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…We are the first to systematically investigate the said relationship using the “simpler” hydride transfer reactions in solution, and our results appear to be consistent with the proposed DAD−Δ E a relationship as well. In our studies, we use structural and solvent effects to modulate the rigidity of the systems and correlate the DAD information with the observed Δ E a ’s. We use the hydride transfer reactions of NADH/NAD + analogues for the study.…”
Section: Introductionsupporting
confidence: 63%
“…(We regard that the TRS structure has the similar geometry as, or close to, the classical TS, except for the distance between the donor/acceptor carbons. ) ,,, The most populated TS structures of the reactions of isopropanol (structure A ) and cyclohexanol ( B and C ) are shown in Figure . From these structures, we found that the 3,4,5-CH 2 –CH 2 –CH 2 – group in cyclohexanol do lead away from the 9-phenyl group of the PhXn moiety.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature study of the DAD−Δ E a relationship for enzyme-catalyzed H-tunneling reactions, the DAD distribution density or enzyme active site rigidity was evaluated from molecular dynamics calculations, , secondary (2°) KIEs on the α-C-H­(D) groups, the information from the two-dimensional IR measurements of the enzyme–coenzyme–inhibitor ternary complex structures, and the stable structures that mimic the productive reactant complexes of the enzymatic reactions. , In our study of the relationship for the hydride-transfer reactions of NADH/NAD + model reactions in solution, we have used the computed distributions of DADs in the productive reactant complexes (PRCs; cf. eq ) as well as the 2° KIEs on N-CH 3 /CD 3 of the reactants to evaluate the tightness of the TRS complexes. ,, Here in this work, we use the Hammett correlations (along with the N-CH 3 /CD 3 2° KIEs) to evaluate the electronic structure and tightness of TRS complexes. The most important discovery is that in all three pairs of reactions (I–III) with substituted acceptors in the same steric environments, a system with a steeper Hammett slope always corresponds with a smaller slope of the Arrhenius plot of KIEs for the reaction of a certain acceptor, i.e., a smaller Δ E a value (see side-by-side comparisons of the two plots in Figures –)!…”
Section: Discussionmentioning
confidence: 99%
“…The DAD sampling concept in the VA-AHT model was initially proposed to explain the change in the T dependence of KIEs for general H-tunneling reactions from enzymes to mutants. ,,, It was subsequently argued that the model may not be used for the adiabatic proton or hydride-transfer reactions in which tunneling may take place from the ground state of the reactant to the excited state of the product at the TRS. The fact, however, is that the hydride-transfer reactions (as well as proton-transfer reactions , ) in enzymes versus mutants frequently demonstrate the same trend of the change in Δ E a ’s as predicted from the VA-AHT model. Several groups did find that Δ E a ’s for the hydride-transfer reactions are correlated to the DAD distributions at the TRS in the same way as described in the model. , , In the meantime, γ-secondary (2°) KIEs for hydride-transfer reactions in enzymes and solution were found to be fitted to this ground state tunneling model, as well. While the commonly accepted tunneling model for hydride-transfer reactions has not been established, these studies indicate that an assumed model somehow contains a DAD−Δ E a relationship. On the other hand, simulations using the ensemble averaged variational TS theory, including multidimensional H tunneling and the empirical valence bond approach, show that the small Δ E a observed in the hydride-tunneling process catalyzed by a dihydrofolate dehydrogenase results from the insensitivity of DADs to temperature. , Nonetheless, study of the said relationship in hydride-transfer reactions will help in the development of hydride-tunneling models and provide insight into the proposed DAD sampling activation in enzyme-catalyzed hydride-transfer reactions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation